2019
DOI: 10.1177/1178221819852641
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Gambling Situations: The Roles of Impulsivity, Substance Use, and Post-Traumatic Stress

Abstract: Gambling disorder and symptoms of post-traumatic stress are highly comorbid. Numerous studies suggest that the presence of one (either disordered gambling or post-traumatic stress) substantially increases the odds of later developing the other. However, little is known about the etiological links between these two domains or the nuances of the comorbidity. Past research has suggested that symptoms of post-traumatic stress might be related to unique motivations for and beliefs about gambling. The present work s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Behavioral endophenotypes are more closely related to the abnormalities that characterize these disorders and have the potential to integrate many different underlying genetic and environmental factors, in effect providing a valuable summary of data that might otherwise be prohibitively difficult or impossible to get (Gottesman and Gould, 2003). One such endophenotype that has been consistently associated with both PTSD and SUD is impulsivity (Weiss et al, 2013;James et al, 2014;Walker et al, 2018;Grubbs and Chapman, 2019). Impulsivity is a multifaceted concept in research but can be broadly defined as a tendency to engage in risky, premature, or situationally inappropriate actions that are characterized by a lack of planning or forethought (Robbins et al, 2012;Jentsch et al, 2014;Dalley and Robbins, 2017).…”
Section: Personality/behavioral Traitsmentioning
confidence: 99%
“…Behavioral endophenotypes are more closely related to the abnormalities that characterize these disorders and have the potential to integrate many different underlying genetic and environmental factors, in effect providing a valuable summary of data that might otherwise be prohibitively difficult or impossible to get (Gottesman and Gould, 2003). One such endophenotype that has been consistently associated with both PTSD and SUD is impulsivity (Weiss et al, 2013;James et al, 2014;Walker et al, 2018;Grubbs and Chapman, 2019). Impulsivity is a multifaceted concept in research but can be broadly defined as a tendency to engage in risky, premature, or situationally inappropriate actions that are characterized by a lack of planning or forethought (Robbins et al, 2012;Jentsch et al, 2014;Dalley and Robbins, 2017).…”
Section: Personality/behavioral Traitsmentioning
confidence: 99%
“…Childhood trauma may compromise the development of neural substrates that provide inhibitory control under stressful conditions (Zhai et al, 2019). Symptoms of trauma have been related to positive gambling expectancies and coping motivations that lead to problematic gambling (Grubbs & Chapman, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has demonstrated that MTurk is a useful resource for studying gambling behavior (Goodie et al, 2013; Kim & Hodgins, 2017). Prior research also suggests that including recreational gamblers (Grubbs & Chapman, 2019; Grubbs et al, 2018) and gamblers with subclinical gambling problems (Weinstock, April, & Kallmi, 2017) in studies of problematic gambling may allow for more accurate assessment of the etiology and mechanistic underpinnings of gambling disorder. Therefore, we chose to recruit a sample that consisted of gamblers across the spectrum of symptom severity rather than focusing only on individuals with gambling disorder.…”
Section: Methodsmentioning
confidence: 99%
“…All participants were recruited via Amazon’s MTurk via the TurkPrime data acquisition platform (Litman, Robinson, & Abberbock, 2017). Subsections of the baseline portions of these data have been analyzed previously (specifically, individuals with Criterion A trauma; Grubbs & Chapman, 2019; Grubbs et al, 2018, 2019). However, the entirety of this data has not been examined in prior literature, nor has the longitudinal aspect of this work.…”
Section: Methodsmentioning
confidence: 99%